2018
DOI: 10.1109/tvlsi.2017.2776561
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of Cost-Effective, High-Throughput LDPC Decoders

Abstract: Abstract-This paper introduces a new approach to costeffective, high-throughput hardware designs for Low Density Parity Check (LDPC) decoders. The proposed approach, called Non-Surjective Finite Alphabet Iterative Decoders (NS-FAIDs), exploits the robustness of message-passing LDPC decoders to inaccuracies in the calculation of exchanged messages, and it is shown to provide a unified framework for several designs previously proposed in the literature. NS-FAIDs are optimized by density evolution for regular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…It can also be observed that, to the best authors knowledge, all paper on finite precision use the "no-decision value", i.e., a Log-Likelihood Ratio (LLR) equal to 0 (without defined sign, thus) in their messages representation. This is also true for the recent work on Non-surjective Finite Alphabet Iterative Decoders (NS-FAIDs) [7] which provides a unified framework for several MS-based decoders like Normalized MS (NMS) decoder, OMS decoder, Partially OMS decoder. In [8], the authors have shown that 3 or 4 bits quantized decoder can benefit from the introduction of particular randomness applied in the amplitude of messages during the decoding process.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It can also be observed that, to the best authors knowledge, all paper on finite precision use the "no-decision value", i.e., a Log-Likelihood Ratio (LLR) equal to 0 (without defined sign, thus) in their messages representation. This is also true for the recent work on Non-surjective Finite Alphabet Iterative Decoders (NS-FAIDs) [7] which provides a unified framework for several MS-based decoders like Normalized MS (NMS) decoder, OMS decoder, Partially OMS decoder. In [8], the authors have shown that 3 or 4 bits quantized decoder can benefit from the introduction of particular randomness applied in the amplitude of messages during the decoding process.…”
Section: Introductionmentioning
confidence: 92%
“…where ξ = 1 + ((d v + 1) mod 2) where d v is the degree of the VN v. Note that the other values of ξ give worse decoding performance. From (7), one can note that, by construction, µ…”
Section: B Sign-preserving Min-sum Decodersmentioning
confidence: 99%
“…We remark that different techniques such as Non-Surjective FAID [17] and Information bottleneck [18] can be used to design Q msg , but these alternative approaches are beyond the scope of this paper.…”
Section: B Flexible Quantizers Of Messages and Channel Outputsmentioning
confidence: 99%
“…In a hardware implemented LDPC decoder, the maximal operating frequency is limited by the length of the longest data path (and so-called, critical path) and f max should be inferior to 1/t D , (f max < 1/t D ), where t D is the length of the critical path to avoid the timing error in run-time [25]. In order to improve the decoding throughput (assuming keeping N , It ave and N c constant), the hardware implementations of LDPC decoders tend to be parallelized to shorten the critical path [22], increasing maximally the achievable operating frequency f max . However, the maximization of the operating frequency in some BF decoders reported in the literature, such as GDBF, PGDBF [14] or MBF [11] may be limited since the global operation still required in these decoders, dramatically increases the critical path [17].…”
Section: The Ppbf Improves the Decoding Throughput And Reduces Thementioning
confidence: 99%
“…, code rate R = 0.50 regular LDPC code [22] (denoted as dv3R050N1296) show that, the MF occupies more than 40% of the total length of the critical path (the details of synthesis setup are introduced in section V). The MF is also a large part of PGDBF in terms of complexity since it requires approximately N − 1 CASUs.…”
Section: Syndromementioning
confidence: 99%